A pictorial key to the sections, groups, and species of the Aedes (Diceromyia) in the Afrotropical Region (Diptera: Culicidae) - Huang, Yiau-Min; Rueda, Leopoldo M. (Zootaxa, 2016)
Nine species of the subgenus Diceromyia Theobald of genus Aedes Meigen in the Afrotropical Region are treated in a pictorial key based on diagnostic morphological features. Images of the diagnostic morphological structures of the adult head, thorax, abdomen, leg and wing are included. The medical importance of the Furcifer Group species in Africa was briefly reviewed.